Corporate debt and investment: A firm level analysis for stressed euro area countries - Stefan Gebauer; Ralph Setzer; Andreas Westphal (European Central Bank (ECB), 2017)
This paper investigates the link between corporate debt and investment for a group of five peripheral euro area countries. Using firm-level data from 2005-2014, we postulate a non-linear corporate leverage-investment relationship and derive thresholds beyond which leverage has a negative and significant impact on investment. The investment sensitivity of debt increased after 2008 when financial distress intensified and firms had a lower capacity to finance investment from internal sources of funds. Our results also suggest that even moderate levels of debt can exert a negative influence on investment for smaller firms or when profitability is low.
Keywords: E22; F34; G31; G32; 330; Corporate debt; leverage; debt overhang; investment; threshold model